ANALYZING THE RELATIONSHIP BETWEEN GREENHOUSE GAS EMISSION AND ECONOMIC GROWTH IN EU ECONOMIES - CAVALIERE, LUIGI PIO LEONARDO; SAEED, AHMED FARHAN; KHATTAK, SANAM WAGMA; KHAN, SUMAIRA YOUSUF (The journal of contemporary issues in business and government, 2021)
It is the consensus among many econometrician and environmental economists that Greenhouse gases like CO2, CH4, N2O, and O3 are the major source of environmental degradation around the globe. EU economies are also suffering from this problem as other economies of the world. The prime objective of this paper is to analyze and gauge the environmental degradation due to economic activities in EU economies. The time series data (1961 to 2017) of economic growth (GDP per capita) has collected from world development indicator and the data of ecological footprint of consumption per capita is collected from Global Footprint Network. The results of Johansson Co-integration and Vector Error Correction model confirms the long run and short run association between both the variables. The economic activities are the main reasons of environmental degradation in the EU economies. EU economies should adopts such policies which reduces the greenhouse gas emissions.